Graduate Employability pada Lulusan Program Studi Administrasi Publik Fakultas Ilmu Administrasi Universitas Brawijaya Tahun 2015 - Muluk, M.R. Khairul; Ulum, M. Chazienul; Widodo, Nurjati (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
The Graduates of Public Administration Study Program is still a gap between the competency of graduates with the actual needs of the workplace. To anticipate and overcome it, it is necessary to do a comprehensive study that involves three elements, namely LO, competencies desired by the work field, and the real conditions of the current graduates. Under ideal conditions, competencies desired by the world of work-which of course is constantly changing throughout the ages-LO must be met by Prodi and by the graduates themselves. Although LO set has been declared in accordance with KKNI, there is still no definitive analysis results and accountability that LO has been in accordance with the actual needs of the working world. Research on Graduate Employability is conducted at the Public Administration of FIA UB that focusing on the achievement of LO associated with skill ability quality of graduates and the needs of the working world.